Safety of vaccine adjuvants: Focus on autoimmunity. Issue 13 (24th March 2015) - van der Laan, Jan Willem; Gould, Sarah; Tanir, Jennifer Y.; ILSI HESI Vaccines; Adjuvants Safety Project Committee
Highlights Industrial, academic, and governmental experts studied vaccine adjuvants safety. Evidence of signals for autoimmune disorders associated with adjuvants was reviewed. Existing adjuvants (used in marketed vaccines) and novel adjuvants were included. The focus was on oil-in-water emulsion and toll-like receptor agonist adjuvants. No compelling evidence was found associating adjuvants and autoimmunity in humans.